2012
DOI: 10.1007/s12325-012-0033-9
|View full text |Cite
|
Sign up to set email alerts
|

Diquafosol Ophthalmic Solution for Dry Eye Treatment

Abstract: Diquafosol ophthalmic solution has a novel mechanism of action that is characterized by its stimulatory effects on tear and mucin secretion. This drug has the potential to be effective in patients with tear film instability and short break-up time type of dry eye, which are essential factors in dry eye pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 12 publications
0
59
0
1
Order By: Relevance
“…Besides inflammatory conditions, there is also an interest in the therapeutic potential of purinergic compounds in a wide range of other pathologies [228] including atherosclerotic vascular diseases [229], cancer [230,231], ocular problems [232], lower urinary tract dysfunction [233], and neurodegenerative disorders including amyotropic lateral sclerosis, multiple sclerosis and Alzheimer's disease [225]. To date only two P2 receptor antagonist are marketed: the irreversible P2Y 12 receptor antagonist clopidogrel (Plavix®), which is used as an antithrombotic agent in patients with atherosclerotic vascular disease [234] and another orally active but reversible antagonist of P2Y 12 , Ticagrelor (Brilinta®), which showed to even have a greater efficacy in reducing cardiovascular death compared with clopidogrel [235].…”
Section: Therapeutic Potential Of P2 Receptor Targetingmentioning
confidence: 99%
“…Besides inflammatory conditions, there is also an interest in the therapeutic potential of purinergic compounds in a wide range of other pathologies [228] including atherosclerotic vascular diseases [229], cancer [230,231], ocular problems [232], lower urinary tract dysfunction [233], and neurodegenerative disorders including amyotropic lateral sclerosis, multiple sclerosis and Alzheimer's disease [225]. To date only two P2 receptor antagonist are marketed: the irreversible P2Y 12 receptor antagonist clopidogrel (Plavix®), which is used as an antithrombotic agent in patients with atherosclerotic vascular disease [234] and another orally active but reversible antagonist of P2Y 12 , Ticagrelor (Brilinta®), which showed to even have a greater efficacy in reducing cardiovascular death compared with clopidogrel [235].…”
Section: Therapeutic Potential Of P2 Receptor Targetingmentioning
confidence: 99%
“…43 The possible mechanism of that action is that DQS ophthalmic solution increases tear-film stability, thus eliminating the vicious cycle (the core mechanism of dry eye on the ocular surface) by increasing fluid secretion, mucin secretion, and membrane-binding mucin gene expression. 13 On the ocular surface of healthy subjects evaluated by meniscometry, an AT reportedly increased fluid volume for~2 min after instillation, and sodium hyaluronate increased the fluid volume for 5 min. 18 The fluid volume at 15 min after instillation of DQS was increased in the SS patients with dry eye and decreased lacrimal gland function.…”
Section: Discussionmentioning
confidence: 99%
“…11 Reportedly, DQS increases tear-film stability on the ocular surface, thereby improving the subjective symptoms and objective signs of dry eye. [12][13][14][15] In addition, DQS exhibits P2Y 2 receptor agonist activity and accelerates fluid transport from the serosal to mucosal (tear) side via chloride channel activation following intracellular calcium ion concentration elevation in the conjunctival epithelium. 16,17 The findings of a previous study suggested that the stimulatory action of DQS on fluid secretion is independent of lacrimal gland function, because the Schirmer test results for a rat model of lacrimal gland removal showed aqueous fluid secretion.…”
Section: Introductionmentioning
confidence: 99%
“…First studies in animal models showed its properties to enhance tear secretion (Fujihara et al, 2001;Murakami et al, 2000Murakami et al, , 2002Yerxa et al, 2002a). These results, as a secretagogue, were the prelude of Diquafosol, an ophthalmic formulation based on this compound, developed as a new treatment for dry eye and was recently approved for marketing in Japan and South Korea (Jacobson et al, 2012;Nakamura et al, 2012).…”
Section: Effect On Tear Secretionmentioning
confidence: 99%
“…Diquafosol has shown its capability to increase the aqueous and mucin portion of tears Nakamura et al, 2012;Takamura et al, 2012;Tauber et al, 2004). In recent years, diquafosol has been used for treating different conditions related with dry eye (Table 2).…”
Section: Effect On Tear Secretionmentioning
confidence: 99%